Adsorption Kinetic and Isotherms Studies of Thiophene Removal from Model Fuel on Activated Carbon Supported Copper Oxide - Ammar, Saad H.; Jaafar, Sama Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
In the present study, activated carbon supported metal oxides was prepared for thiophene removal from model fuel (Thiophene in n-hexane) using adsorptive desulfurization technique. Commercial activated carbon was loaded individually with copper oxide in the form of Cu2O/AC. A comparison of the kinetic and isotherm models of the sorption of thiophene from model fuel was made at different operating conditions including adsorbent dose, initial thiophene concentration and contact time. Various adsorption rate constants and isotherm parameters were calculated. Results indicated that the desulfurization was enhanced when copper was loaded onto activated carbon surface. The highest desulfurization percent for Cu2O/AC and origin AC at initial thiophene concentration of 500 ppm, adsorbent dose of 0.01 g/ml and equilibrium time of 5 hr were 87.4% and 53.4% respectively, for outlet concentration of 63 mg/L for copper oxide and 236 mg/L for original AC. Generally, the percent removal of thiophene increases with the increase in adsorbent dose and decrease with increase in initial thiophene concentration. The present study was mainly focusing on the kinetics and adsorption isotherms aspect; adsorption kinetics of thiophene onto activated carbon supported Cu2O adsorbent was closely represented by the second order kinetic model and Freundlich isotherms well represented the equilibrium adsorption of thiophene from model fuel.